2008
DOI: 10.2134/agronj2007.0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Defoliation Management on Water‐Soluble Carbohydrate Energy Reserves, Dry Matter Yields, and Herbage Quality of Tall Fescue

Abstract: Pasture Management 122A grono my J our n al • Volu me 10 0 , I s sue 1 • 2 0 0 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
54
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 15 publications
12
54
1
9
Order By: Relevance
“…In parallel, the non-structural carbohydrate concentration decreases and remains at low values ( Figure 3B) unless defoliation pressure is suppressed, resulting in non-structural carbohydrate concentration and LER recovery. This illustrates that under repeated and frequent defoliation, carbohydrate reserves may not re-accumulate to a sufficient level between two consecutive defoliations and therefore may reduce LER, as confirmed in other studies [87][88][89][90]. These observations on isolated plants are in line with field data on tall fescue under continuous sheep grazing, showing that the LER of grazed tillers was substantially decreased compared with the LER of undefoliated tillers [91].…”
Section: Leaf Growth Ratesupporting
confidence: 89%
“…In parallel, the non-structural carbohydrate concentration decreases and remains at low values ( Figure 3B) unless defoliation pressure is suppressed, resulting in non-structural carbohydrate concentration and LER recovery. This illustrates that under repeated and frequent defoliation, carbohydrate reserves may not re-accumulate to a sufficient level between two consecutive defoliations and therefore may reduce LER, as confirmed in other studies [87][88][89][90]. These observations on isolated plants are in line with field data on tall fescue under continuous sheep grazing, showing that the LER of grazed tillers was substantially decreased compared with the LER of undefoliated tillers [91].…”
Section: Leaf Growth Ratesupporting
confidence: 89%
“…For example, Cros et al (2003) reported llS of 500°C-days for perennial ryegrass, 600°C-days for cocksfoot (Dactylis glomerata l.), or 700°C-days for tall fescue (Festuca arundinacea Schreb). This is consistent with the recommended increase in the inter-defoliation interval for these species when the interval is based on leaf-stage (Rawnsley et al 2002;Turner et al 2006;Donaghy et al 2008).…”
Section: Lls M(r1 Em)supporting
confidence: 87%
“…The greater WSC content per stubble at 4-leaf stage (Figure 4) in our study has been supported by similar results reported by , , using several perennial grasses. Further, Donaghy et al (2008) reported a 33 to 43% greater WSC content for stubble of tall fescue harvested at 4-leaf stage relative to 2and 3-leaf stages. The range of difference in WSC content in our study was 21 to 35% greater at 4-leaf stage than at 2-leaf stage.…”
Section: Discussionmentioning
confidence: 93%
“…Both stubble WSC concentration and content were greater for Maximus than for Marshall and there was a positive, but weak correlation between WSC content and crop growth rate (r = 0.299; p = 0.039) in our study, and therefore, the role of WSC on the difference in forage harvested between Maximus and Marshall is unclear. Other studies have reported a strong positive linear relationship between WSC concentration and content on the regrowth of several forage grass species (Donaghy & Fulkerson, 1998;Donaghy et al, 2008;Lee et al, 2009;. Yet, other reports have pointed to the inconsistency in this relationship (Donaghy & Fulkerson, 1998;Richards & Caldwell, 1985;White, 1973) and that other factors such as N reserve in the stubble (Thornton & Millard, 1997;, the contribution of stored WSC in the roots (Caldwell, Richards, Johnson, Nowak, & Dzurec, 1981) and the concurrent occurrence of photosynthesis (leaf area post-defoliation) at the canopy level (Donaghy & Fulkerson, 1997;Richards & Caldwell, 1985) are equally important in forage grass regrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation